Information Women Choose to Receive About Prenatal Chromosomal Microarray Analysis. Issue 1 (January 2020) - Hochner, Hagit; Daum, Hagit; Douiev, Liza; Zvi, Naama; Frumkin, Ayala; Macarov, Michal; Kimchi-Shaal, Adva; Hacohen, Nuphar; Eilat, Avital; Faham, Duha; Shkedi-Rafid, Shiri
Abstract : OBJECTIVE: To examine the choices of women with both high-risk and low-risk pregnancies who are undergoing prenatal chromosomal microarray analysis in a clinical setting regarding three challenging types of findings: variants of uncertain clinical significance, susceptibility loci for neurodevelopmental disorders, and copy number variants associated with risks for adult-onset conditions. We assessed whether women's choices were associated with indications for testing or with one-on-one pretest genetic counseling. METHODS: In this cross-sectional study, medical records of women who underwent invasive prenatal chromosomal microarray analysis testing (N=1, 070) at Hadassah Medical Center between June 2017 and February 2018 were examined for testing indications, choices regarding chromosomal microarray analysis findings, and type of pretest genetic counseling. Multivariable analyses to assess associations with testing indication and prior genetic counseling were carried out using logistic regression models. RESULTS: In total, 56% of women (n=593) chose to be informed of all three types of findings and 20% (n=218) chose not to be informed of any of the findings beyond high-penetrance childhood-onset pathogenic findings. Variants of uncertain clinical significance as a single choice was the least-selected finding (2.5%, n=27). Low-risk pregnancies (ie, those with normal biochemical screening and fetal ultrasound examinations) were associated with increased interest in receiving genetic information about adult-onset conditions (adjusted odds ratio [aOR] 1.7; 95% CI 1.18–2.33) and susceptibility loci (aOR 1.5; 95% CI 1.08–2.10). CONCLUSION: Women with both high-risk and low-risk pregnancies were generally more likely to choose to receive additional genetic information, albeit differences in preferences depend on testing indication and type of pretest counseling. Abstract : Pregnant women undergoing invasive prenatal testing are generally desirous to be told about variants of uncertain clinical significance and adult-onset genetic information.